2018
DOI: 10.37358/mp.18.4.5072
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Encapsulated Nanomaterials with Application in Medical Area

Abstract: Novel materials belonging to the class of anionic clays are synthesized by investigating their properties at nano scale. Thus, hydrotalcites or layered double hydroxides (LDHs) were used as drug delivery carriers in order to prevent or to treat infections produced by some pathogen agents. Their physical and chemical properties allow them to include different molecules in the interlayer space and then to ensure their transport to the target. The current work reveals the obtaining of nanohybrid compounds type am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Yariktas et al observed that an increased level of free oxygen radicals may contribute to development of otitis media with effusion [29,30] and antioxidant vitamins can be added to the treatment. Cemek et al found higher MDA serum values in children with acute tonsillitis and acute otitis media and lower values of antioxidant vitamins [31,32].…”
Section: Resultsmentioning
confidence: 98%
“…Yariktas et al observed that an increased level of free oxygen radicals may contribute to development of otitis media with effusion [29,30] and antioxidant vitamins can be added to the treatment. Cemek et al found higher MDA serum values in children with acute tonsillitis and acute otitis media and lower values of antioxidant vitamins [31,32].…”
Section: Resultsmentioning
confidence: 98%
“…This system should be regarded as an integrated subsystem of the human body, any local manifestation having the potential to induce general changes, and these may also affect the homeostasis of the stomatognat system. [41][42][43] There are no specific pathognomonic oral lesions that may appear in diabetes, but the stomatognat system components are affected by illnesses that have an increased incidence, a more serious development, and more common complications in patients with DM than in others [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen expresion suppression and progesterone receptors activation represent the essential target for current drugs, and also for research and new drugs development. The most used and studied agents for endometriosis treatment are oral GnRH antagonists, aromatase inhibitors SERMs (Selective Estrogen Receptors Modulators) and SPRMs [17][18][19]. UPA is generally prescribed for conservative treatment of fibroids to preserve fertility.…”
Section: Resultsmentioning
confidence: 99%